Determination of Optimum Harvesting Time for Periphyton Production on Artificial Substrates (Progressive Agriculture, 2013)
The experiment was conducted in two cement made cisterns for a four-week period. Important physico-chemical water quality parameters and harvesting time in periphyton production were studied. During the study period, four groups of phytoplankton and two groups of zooplankton were observed. Among phytoplankton, Chlorophyceae was the most dominant having 62% Chlorella followed by Bacillariophyceae having 15% Navicula and 12% Cyclotella, Cyanophyceae having 5% Oscillatoria and 2% Anabaena and Euglenophyceae having 2% Euglena and 1% Phacus. The grand averages of periphyton mass production were 0.569 (± 0.242) mg DM/cm2 in C-1. There was highly significant (p